Teacher Spiritualism: The Vocation Within - Herrera, Luis Javier Pentón (Cultural and religious studies, 2016)
Ancient civilizations adopted an early education system that included religion as an integral part of its focus. For this reason, priests, monks, and other people of faith, were trusted with the important task of educating their community and instructing them in the values, beliefs, and norms of their society. As time passed, public education continued to evolve to keep up with the societal demands to the point that education and religion were not longer connected. Simultaneously, professionals in the education field have also changed and educators are no longer required to be people of faith. However, considering that the mission of education has remained the same, it would be unrealistic to consider teachers as unspiritual individuals regardless of their religious beliefs and affiliations. This paper explores the idea that educators are innate spiritual individuals who strive to perpetuate the norms, values and virtues of their society. In addition, this article presents the concept of teacher spiritualism as a contemporary reality of our teachers and our educational system.